Training Positive Rumination in Expressive Writing to Enhance Psychological Adjustment and Working Memory Updating for Maladaptive Ruminators - Yang, Hongfei; Li, Huizhong (Frontiers in Psychology, 2020)
Rumination is associated with psychological adjustment and working memory (WM) capacity. Studies have shown that psychological interventions can reduce negative rumination and improve psychological adjustment and WM capacity. The present study investigated the effect of positive rumination training in expressive writing on psychological adjustment and WM updating capacity. Within an experimental design, positive rumination was manipulated for 10 participants who were maladaptive ruminators in an experiment using a 5-week training compared to the control group with nine participants. Results revealed significant enhancement of psychological adjustment and the response time (RT) of WM updating in the experimental group but not in the control group. The two groups did not show significant difference of all the variables in pretest. However, the experimental group showed significantly better outcomes than the control group in posttest. The results suggest that positive rumination training in expressive writing is effective and rumination has a causal influence on WM updating capacity.